Double-phase liquid membrane extraction for the analysis of pesticides - Mohd. Marsin Sanagi, author; Nurul Auni Zainal Abidin, 1985-, author; See, Hong Heng 1980-, author; Wan Aini Wan Ibrahim, author; Symposium on Analytical Sciences (2007: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL